Short-term and long-term outcomes in living donors for liver transplantation: Cohort study. (December 2020) - Takagi, Kosei; Umeda, Yuzo; Yoshida, Ryuichi; Watanabe, Nobuyuki; Kuise, Takashi; Yoshida, Kazuhiro; Yasui, Kazuya; Matsuda, Tatsuo; Fujiwara, Toshiyoshi; Yagi, Takahito
Abstract: Background: Although perioperative outcomes following donor hepatectomy (DH) have been reported, little is known about the long-term outcomes in living donors of liver transplantation. The aim of this study was to investigate the short-term and long-term outcomes following DH. Methods: A total of 408 living donors who underwent DH between 1996 and 2019 were analyzed in this retrospective study, focusing on short-term outcomes with respect to the operation period (era) and the graft type, as well as long-term outcomes. Results: The overall incidence of postoperative complications was 40.4%. These included minor (30.4%), major (10.0%), and biliary (14.0%) complications. Short-term outcomes after DH slightly improved over time, and outcomes did not differ significantly between the graft types. With regards to long-term outcomes, the incidence of surgery-related complications such as keloids, incisional hernias, and mechanical bowel obstructions was 6.6% over a median follow-up of 7.2 years. In addition, some donors developed comorbidities such as lifestyle diseases and cancers during the follow-up period. Conclusions: Our study confirmed an improvement of perioperative outcomes in living donors. There was no significant association between the graft type and postoperative outcomes. Donors could develop various morbidities during long-term follow-up. Therefore, a careful perioperative management and long-term follow-up should be provided to living donors. Highlights: Short-term and long-term outcomes were investigated in 408 living liver donors. Short-term outcomes included 10% major complications and 14% biliary complications. Short-term outcomes after donor hepatectomy have slightly improved over time. Incidence of surgery-related complications during the follow-up period was 6.6%. Careful perioperative care and long-term follow-up should be provided to donors.